NILAI TAMBAH DAN PENYERAPAN TENAGA KERJA PADA INDUSTRI KECIL TEMPE DI DESA PANARUKAN KECAMATAN KEPANJEN KABUPATEN MALANG - Wahyunindyawati Wahyunindyawati; Asnah Asnah (BUANA SAINS, 2008)
The objective of this study were to analyze cost structure, added value and profit as well as absorption, incentives and labour share of tempe small scale industry. This study was conducted at a tempe production centre of Panarukan Village, Kepanjen District of Malang Regency. The analytical methods used were cost structure and added value analyses. Results of this study showed that for each process needed cost of more than Rp 181.000, that was dominated (90%) by variable costs. The net profit of each process was more than Rp 100.000. Conversion factor reached 2,86 and added value reached more than Rp 1.400 (added value ratio 21,44%), consisting profit of Rp 1.184,55/kg of row material (profit rate 54,46%) and labour incentive of Rp 218,01/kg of row material (labour share 14,86%). The labour absorption reached 1 MDE/process that was mostly family labour. Producer added value reached Rp 1.402/kg of row material, most of them as net profit and labour incentives